Best Answer

6ab / 3b = 2a

so

b / b cancels each other out

6 / 3 = 2 / 1

Example: a = 4 and b = 5

6ab = 6 x 4 x 5 = 120

3b = 3 x 5 = 15

120 / 15 = 24 / 3 = 8 = 2a = 2 x 4

Lvl 1

-9a+3b-6ab

Q: What is the simplification of 6ab over 3b?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

2a x 3b = 6ab

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b

3a2b is the simplest formImproved Answer:-3a x 2b = 6ab when simplified

6a^2 - 6ab + 7a^2 = 13a^2 - 6ab = a * (13a - 6b)

12ab

Related questions

6ab-3b factorize = 3

2a x 3b = 6ab

0.3333

2a x 3b = 6ab

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b

2,3,2a,3a,3b,2b,3b^2,2b^2

6a^b-18ab^2+24ab

With the assumption your asking what a or b are in terms of each other. a=3b/(6b-2) b=2a/(6a-2)

3a2b is the simplest formImproved Answer:-3a x 2b = 6ab when simplified

5a2 + 6ab=a(5a+6b)

6a^2 - 6ab + 7a^2 = 13a^2 - 6ab = a * (13a - 6b)

Since 3a is a factor of 6ab, it is automatically the GCF.